Investigating the variations in the composition and heating of interacting ICMEs - Srivastava, Nandita; Mirtoshev, Zavkiddin; Mishra, Wageesh (Frontiers in Astronomy and Space Sciences, 2023)
Interacting CMEs have been commonly reported during STEREO era. With the interaction of CMEs in the heliosphere, it is expected that the participating CMEs will either merge to form a single ICME or will arrive as distinct entities or ICMEs at 1 AU. Earlier studies have focussed on in-situ observations of solar wind i.e., plasma and magnetic field properties to understand the nature of CME-CME interaction and its impact. In this paper, we examine the observations of composition parameters of those ICMEs which resulted due to interaction of two CMEs during their propagation between the Sun and the Earth. We report two events of CME-CME interaction observed in 2012, of which one led to a merged structure after interaction, as observed at 1 AU. The second interaction event was reported to arrive at L1 as two distinct structures. Our analysis reveals distinct composition signatures in the form of ion-charge states enhancements. The results improve our understanding of the signatures of ICMEs, and different complex structures formed after interaction. The study reveals that compression can occur due to the passage of the shock associated with the following CME through the preceding CME, and not due to CME-CME interaction. The results also highlight the importance of comparison of solar wind proton velocity data with the expected temperature data in particular to understand the ICME-ICME interaction processes.